1999
DOI: 10.1152/ajpheart.1999.276.1.h317
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac ANG II postmyocardial infarction in rats: effects of nephrectomy and ACE inhibitors

Abstract: We evaluated in rats the time course of changes in cardiac versus plasma ANG I and II postmyocardial infarction (MI) and the effects of nephrectomy and angiotensin-converting enzyme (ACE) inhibitors on the early changes post-MI. Acute coronary artery ligation was induced in conscious rats using the two-stage model, and plasma and cardiac tissue were obtained shortly (6 h, 1 and 3 days) and chronically (1, 4, and 8–9 wk) after MI. In an additional group of rats, bilateral nephrectomy was performed 18 h before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…MI was induced by ligation of the left ascending coronary artery (LAD) as described previously (11)(12)(13). In short, after left-sided thoracotomy, the left coronary artery was occluded 2 to 5 mm from its origin with a 6.0 silk suture.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…MI was induced by ligation of the left ascending coronary artery (LAD) as described previously (11)(12)(13). In short, after left-sided thoracotomy, the left coronary artery was occluded 2 to 5 mm from its origin with a 6.0 silk suture.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Cell lysates were centrifuged and extracted on Sep-Pak 18 cartridges. Angiotensin peptides were assessed by radioimmunoassay (RIA) after separation on high-performance liquid chromatography (HPLC) (20,22).…”
Section: Angiotensin I and Ii Assaymentioning
confidence: 99%
“…[47][48][49][50] Although its levels in the heart are several times higher than those measured concomitantly in plasma, this does not necessarily imply that Ang II is synthesized in the heart by locally synthesized renin, angiotensinogen, and ACE. First, Ang II present in the heart may have been taken up from the circulation via AT 1 receptor-mediated endocytosis, 51 and second, if local Ang II synthesis has occurred, it may depend on RAS components that are also taken up from the circulation.…”
Section: Ang II Synthesis In the Heart Under Normal Conditionsmentioning
confidence: 99%
“…This approach will lead to an overestimation of the true angiotensin levels or even to the detection of angiotensins in medium that does not contain angiotensins. It should also be kept in mind that in view of the cardiac angiotensin levels measured in vivo, with the use of appropriate prior purification and separation (Ang I, Ϸ5 fmol/g wet wt; Ang II, Ϸ20 fmol/g wet wt), 47,48,49,50 even levels of 5 to 10 fmol/mL are very high, because in most studies, medium was collected from only 1 to 10 million cells, with an estimated wet weight far below 1 g. Sadoshima et al 77 found the Ang II concentration in the medium of serum-deprived cardiomyocytes to increase nearly 100-fold on stretch. This Ang II, which is assumed to be responsible for the hypertrophic 59,77,79,80 or apoptotic 81 response of cardiomyocytes after stretch, appeared to originate from intracellular storage sites, inasmuch as its release was not affected by captopril and not accompanied by Ang I release.…”
Section: Stretch-mediated Ang II Release Frommentioning
confidence: 99%
See 1 more Smart Citation